Reaction times to morphologically inflected nonwords: a study of second language learners of English - Cilibrasi, Luca; Jiránková, Lucie (Journal of Monolingual and Bilingual Speech, 2021)
Previous work has shown that monolingual speakers of English are sensitive to the presence of inflectional morphology when it is applied to nonwords. For example, when a nonword ends in a sequence of phonemes that respect the morphophonological rules regulating tense inflection, speakers are slower in recognising it. In this study, we investigated whether a similar pattern applies to second language learners as well. 91 learners of English with Czech as L1 where presented with a same/different minimal pairs task containing nonwords with various endings (in one condition, a sequence of phonemes that could be interpreted as an inflectional morpheme). Consistently with research on monolingual participants, the study showed that also second language learners are slower in processing nonwords that contain potential inflectional morphemes. The pattern was observed from low levels of proficiency, suggesting that learners are sensitive to these rules from early stages of learning.